Ambidextrous practices in public service organizations: innovation and optimization tensions in Dutch water authorities. Issue 3 (3rd March 2020) - Gieske, Hanneke; Duijn, Michael; van Buuren, Arwin
ABSTRACT: For public service organizations (PSOs) it is essential to be able to simultaneously optimize and innovate policies, processes and services. This article explores how PSOs shape these dual practices by examining optimization and innovation practices in eight Dutch regional water authorities (RWAs) using focus groups. It uncovers mutually reinforcing differences in culture, strategy and management leading to different ambidextrous configurations. In low ambidextrous RWAs a legalistic task-orientation goes along with a transactional management style and focus on optimization only. In high ambidextrous RWAs a societal value-orientation, integrative strategies, and a more transformational management style lead to more embedded innovation practices.